Stochastic description of the dynamics of thrombo-embolus in an arterial compartment - Egenti, Nzerem Francis; Ukamaka, Orumie Cynthia (International Journal of Advanced Mathematical Sciences, 2015)
Thrombosis, the formation or presence of blood clot in an arterial segment, most often admit the detachment of an embolus which flows antegrade. Embolism, the blockage of artery by an embolus, is a medical emergency. In a bid to gain an insight into its deleteriousness, we studied the diffusion of the embolus in an arterial compartment by means of Fokker-Planck equation, and the eventual occlusion of a site of the artery where the embolus was lodged. The probability density function of its spatial coordinate at any time was the hallmark of the diffusion process. Analytic solution of the emerging stochastic equation was sought. This study implicated thrombo-embolism in cardiovascular events.